SYNERGY BETWEEN STUDENTS AND THE COMMUNITY IN REALIZED EMPOWERMENT OF LOCAL POTENTIAL IN SUNGAI RENGAS VILLAGE - Rapu Dode, Willibald Julio Alvares; Oktarianti, Sherly; Margareta Siahaan, Yesika Aprialia (Dianmas Bhakti: Jurnal Pengabdian pada Masyarakat, 2025)
Community Service Program (Kuliah Kerja Nyata / KKN) is a form of student dedication to society through the direct application of knowledge, technology, and skills in the field. The 2025 KKN program in Sungai Rengas Village, Kubu Raya Regency, West Kalimantan, was carried out under the theme “Synergy between Students and the Community in Realizing Local Potential Empowerment.” The main objective of this program was to enhance awareness, skills, and community participation in utilizing village potentials, particularly in agriculture, fisheries, and the processing of local products with economic value. The methods applied included observation, socialization, training, mentoring, and the implementation of work programs oriented towards community needs. The results showed an increase in community knowledge and skills, the creation of processed products based on local resources, and the establishment of closer collaboration between students and the community. This program also fostered collective awareness to preserve and develop local potentials as capital for sustainable village development. Thus, the synergy between students and the community in KKN activities provides not only short-term benefits in terms of capacity building but also long-term contributions to the independence and empowerment of Sungai Rengas Village. Keywords: KKN, student-community synergy, empowerment, local potential, Sungai Rengas Village